Carbon-rich cyclopentadienyl ruthenium allenylidene complexes - Spörler, Susanne; Strinitz, Frank; Rodehutskors, Philipp Maximilian; Müller, Lisa; Waterloo, Andreas; Dürr, Maximilian; Hübner, Eike; Ivanovic-Burmazovic, Ivana; Tykwinski, Rik; Burzlaff, Nicolai (New Journal of Chemistry, 2016)
Ruthenium allenylidene complexes with carbon-rich polyaromatic moieties have been synthesized by using [RuCl(η-CH)(PPh)] (η-CH = cyclopentadienyl) as a precursor and the propargyl alcohols 10-ethynyl-10-hydroxyanthracen-9-one (ACO), 13-ethynyl-13-hydroxypentacen-6-one (PCO), 1-phenyl-1-(pyren-1-yl)prop-2-yn-1-ol (PyrPh), 9-ethynyl-9H-fluoren-9-ol (FN) and 6-ethynyl-6H-benzo[cd]pyren-6-ol (BPyr) as ligands. The resulting cationic allenylidene complexes, [Ru(η-CH)(CC(AO))(PPh)]PF (1), [Ru(η-CH)(CC(PCO))(PPh)]PF (2), [Ru(η-CH)(CC(PyrPh))(PPh)]PF (3), [Ru(η-CH)(CC(FN))(PPh)]PF (4), and [Ru(η-CH)(CC(BPyr))(PPh)]PF (5) show interesting intermolecular π-interactions in the solid-state structure as well as solution state complexation with pyrene (documented by Job's plots experiments). CV data indicate possible Ru(ii)/Ru(iii) oxidation, as well as the potential reduction of the carbon-rich allenylidene moiety.